Zad 1 (3+3pkt) ZAPISZ ROZWIĄZANIE ORAZ SPRAWDZENIE. Rozwiąż równanie: a) 3x + 7 = 2x + 1

d) 7-2x = 5x + 28

b) x = 8 - 3x

e) 8x–5= 9x - 5

c) 2x - 4 = 4x -2

f) 6x + 2x - 10 = 3x + 5

a) 3x + 7 = 2x +1

Jest tak jak ma być czyli nie pokolei bo zle wczytało
Na dziś!._.​


Odpowiedź :

[tex]a) \\\\3x+7=2x+1\\3x-2x=1-7\\x=-6\\\\d) \\\\7-2x=5x+28\\-2x-5x=28-7\\-7x=21 /:-7\\x=-3\\\\b) \\x=8-3x \\x+3x=8 \\4x=8/:4\\x=2\\\\e) \\\\8x-5=9x-5\\8x-9x=-5+5\\-x=0\\x=0\\\\c) \\\\2x-4=4x-2\\2x-4x=-2+4\\-2x=2/:(-2)\\x=-1\\\\f)\\\\6x+2x-10=3x+5\\8x-10=3x+5\\8x-3x=5+10\\5x=15/:5\\x=3\\[/tex]

Odpowiedź:

a)

3x + 7 = 2x + 1

3x - 2x -= 1 - 7

x = -6

spr.

L = 3 * (-6) + 7 = -18 + 7 = -11

P = 2 * (-6)  + 1 = -12 + 1 = -11

L = P

d)

7-2x = 5x + 28

-2x - 5x = 28 - 7

-7x = 21      /:(-7)

x = -3

spr.

L = 7 - 2(-3) = 7 + 6 = 13

P = 5 * (-3) + 28 = -15 + 28 = 13

L = P

b)

x = 8 - 3x

x + 3x = 8

4x = 8     /:4

x = 2

spr.

L = 2

P = 8 - 3 * 2 = 8 - 6 = 2

L = P

e)

8x–5= 9x - 5

8x - 9x = -5 + 5

-x = 0

x = 0

spr.

L = 8 * 0 - 5 = -5

P = 9 * 0 - 5 = -5

L = P

c)

2x - 4 = 4x -2

2x - 4x = -2 + 4

-2x = 2     /:(-2)

x = -1

L = 2 * (-1) - 4 = -2 - 4 = -6

P = 4 * (-1) - 2 = -4 - 2 = -6

L = P

f)

6x + 2x - 10 = 3x + 5

8x - 3x = 5 + 10

5x = 15      /:5

x = 3

spr.

L = 6 * 3 + 2 * 3 - 10 = 18 + 6 - 10 = 24 - 10 = 14

P = 3 * 3 + 5 = 9 + 5 = 14

L = P

a)

3x + 7 = 2x +1

3x - 2x = 1 - 7

x = -6

spr.

L = 3 * (-6) + 7 = -18 + 7 = -11

P = 2 * (-6) + 1 = -12 + 1 = -11

L = P

Szczegółowe wyjaśnienie: